The fibularis longus muscle revisited: comparative anatomy, developmental perspectives, and clinical relevance - Landfald, Ingrid C.; Ciechanowska, Magdalena; Olewnik, Łukasz (Frontiers in Cell and Developmental Biology, 2025)
BackgroundThe fibularis longus tendon (FLT) shows substantial anatomical variability, yet its clinical and developmental implications are incompletely characterised. Classification systems derived from fetal and adult morphology may improve diagnostic interpretation and surgical planning.ObjectiveTo synthesise comparative, ontogenetic, radiological and surgical perspectives on the FLT into a unified, classification-aware framework.Materials and methodsAnatomical data from two previously published cohorts—one fetal (n = 94 lower limbs) and one adult (n = 100 lower limbs)—were reviewed to evaluate distal insertion morphotypes. Findings were correlated with imaging literature (MRI, ultrasound) and appraised for diagnostic pitfalls and practical applicability.ResultsAcross fetal and adult material, three principal distal insertion types were identified: Type I (single insertion), Type II (bifurcated) and Type III (trifurcated in fetuses or fusion variants in adults). Trifurcated Type III appears confined to prenatal specimens, whereas adult Type III reflects secondary postnatal fusion with neighbouring structures. Radiological correlation highlights recurring misinterpretations involving accessory bands and fusion patterns. Classification-aware interpretation suggests that surgical risk can differ by FLT type, particularly in tendoscopic assessment and tendon transfer planning.ConclusionA unified classification aligning fetal and adult variants provides a clinically relevant scaffold for preoperative planning, radiological reporting and anatomical research. Consistent recognition and reporting of FLT subtypes may reduce diagnostic error, inform procedural strategy and enhance anatomical education.